Role of endoanal ultrasound in the assessment of perianal fistula in correlation with MRI fistulography - Alaa Sayed; Hatem Mohamed Said El-azizi; Mohamed Yehia Ahmed El-barmelgi; Heba Azzam (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background Perianal fistula is a considered as chronic recurrent inflammatory condition that requires proper surgical treatment and may require repeated intervention. Therefore, adequate pre-operative radiological diagnosis plays a critical role. In this study, we aimed at comparing the role of endoanal ultrasonography with MRI fistulography in evaluating the primary fistula's tract, internal opening, secondary extensions, and complications of the perianal fistula. Results The study was carried over 108 males (90%) and 12 females (10%) presenting with clinically diagnosed perianal fistula. Ultrasound was found superior to MRI in the localization of the internal opening with estimated K value (0.44), P value (0.001). Regarding the type of fistula, ultrasound was found in agreement with MRI in 112 cases (93.3%) with estimated K value of about (0.7). Ultrasound was found equally effective as MRI in the detection of complication with estimated agreement K value of about 1. Regarding assessment of the secondary extensions, the agreement between the two modalities was about 50% with estimated k value of about 0.65. Conversely, MRI was found superior to ultrasound in the characterization of the fibrotic tracts. Conclusions Both EAUS and MRI have a crucial role in the evaluation and detection of perianal fistulas. EAUS was preferable to MRI in the localization of the internal opening; ,conversely, in the evaluation of extra-sphincteric fistulas and fibrotic tracts characterization MRI was preferable to EAUS.